-2(2y-6)-y=-2(y-3)

Simple and best practice solution for -2(2y-6)-y=-2(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2y-6)-y=-2(y-3) equation:


Simplifying
-2(2y + -6) + -1y = -2(y + -3)

Reorder the terms:
-2(-6 + 2y) + -1y = -2(y + -3)
(-6 * -2 + 2y * -2) + -1y = -2(y + -3)
(12 + -4y) + -1y = -2(y + -3)

Combine like terms: -4y + -1y = -5y
12 + -5y = -2(y + -3)

Reorder the terms:
12 + -5y = -2(-3 + y)
12 + -5y = (-3 * -2 + y * -2)
12 + -5y = (6 + -2y)

Solving
12 + -5y = 6 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
12 + -5y + 2y = 6 + -2y + 2y

Combine like terms: -5y + 2y = -3y
12 + -3y = 6 + -2y + 2y

Combine like terms: -2y + 2y = 0
12 + -3y = 6 + 0
12 + -3y = 6

Add '-12' to each side of the equation.
12 + -12 + -3y = 6 + -12

Combine like terms: 12 + -12 = 0
0 + -3y = 6 + -12
-3y = 6 + -12

Combine like terms: 6 + -12 = -6
-3y = -6

Divide each side by '-3'.
y = 2

Simplifying
y = 2

See similar equations:

| 2a-4=3(a-4) | | x^2+(1-i)x-1=0 | | 2(2y-1)=-19 | | -32+8v=6(v-7) | | 2b^2+3b-2= | | -42=3(6+8b)+6(-3b-7) | | 9x-2=133 | | 60=-5(6n-6) | | 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x | | 2(3-x)=60 | | -5.5=-3.4 | | 7(x-2)=5(x-4) | | -7(7n+7)=39-5n | | 3+r=19 | | 10b^2-15b-8b+12b=0 | | 12x^4+10x^3-12x^2=0 | | -3n-2(-8n-3)=-14+3n | | 6x+12+54=180 | | 18x+6=19x | | 2(2p-3)=36-2p | | 8(8x-1)+4(1+8x)=-4 | | -23=6x+2 | | 16x^2-72x+75=0 | | 9x+6=-36 | | 32=-6x+2 | | 69-1=9+20 | | 17x+20=16x+20 |

Equations solver categories